2012
DOI: 10.1108/14636641211254905
|View full text |Cite
|
Sign up to set email alerts
|

Applications of interpersonal circumplex and complementarity theory to staff‐prisoner relationships

Abstract: PurposeThe current study aims to examine staff‐prisoner relationships through an exploration of interpersonal style. It was predicted that the interpersonal style of prison officers would impact on their perception of their ability to work with prisoners, dependent on the specific interpersonal style of prisoners.Design/methodology/approachPrison officers (n=128) completed a measure of interpersonal style (Check List of Interpersonal Transactions‐Revised: CLOIT‐R) and a series of eight vignettes designed to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Based on an exploratory proposition, it can be suggested that crisis negotiators are friendly and positive in their crisis negotiation approach with all types of forensic inpatient (Bailey & Ireland, 2006) and, as such, are deemed friendlysubmissive in their interpersonal style. In agreement with Gredecki's (2008) recognition of literature that identifies positive interpersonal styles of prison officers and prisoners within a prison setting, this study suggests that the assumption of the indiscriminate friendly/positive approach towards forensic inpatients challenges interpersonal complementarity theory. It can be argued that complementing interpersonal style will encourage better interaction (Gredecki, 2008) rather than limiting the success of a relationship by recruiting crisis negotiators with a similar interpersonal style.…”
supporting
confidence: 65%
See 2 more Smart Citations
“…Based on an exploratory proposition, it can be suggested that crisis negotiators are friendly and positive in their crisis negotiation approach with all types of forensic inpatient (Bailey & Ireland, 2006) and, as such, are deemed friendlysubmissive in their interpersonal style. In agreement with Gredecki's (2008) recognition of literature that identifies positive interpersonal styles of prison officers and prisoners within a prison setting, this study suggests that the assumption of the indiscriminate friendly/positive approach towards forensic inpatients challenges interpersonal complementarity theory. It can be argued that complementing interpersonal style will encourage better interaction (Gredecki, 2008) rather than limiting the success of a relationship by recruiting crisis negotiators with a similar interpersonal style.…”
supporting
confidence: 65%
“…This is the first research study looking at the interpersonal relationship between crisis negotiators and forensic inpatients within the forced-contact environment (Gredecki, 2008) of a secure forensic hospital. Submissive interpersonal style demonstrated a difference between crisis negotiators, clinical workers and students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not the case in many countries, where prisoner–officer relationships are hostile (Blagden et al , 2017), which may cause further obstacles for successful MI implementation and adherence. Other potential issues include problems of role duality (Zur, 2015), which could manifest as a lack of prisoner empathy needed for MIs (Gredecki and Ireland, 2012), particularly if they have personal conflicts (Barry, 2020). As positive prisoner–prison staff relationships are a protective factor for programme adherence (Buric et al , 2023), the role of officers within MIs is recommended to be carefully considered on an individual prison basis.…”
Section: Discussionmentioning
confidence: 99%